(untitled) (Journal Of Educational and Psychological Researches, 2022)
The research aimed to find the effectiveness of teaching impact of the reflex learning strategy on the fifth class female student achievement of the geography content material). The researcher adopted the null hypotheses (there are no statistically significant differences at (0,05) level between the women score mean of the experimental group student who has been taught by the cement material assigned by the reflex learning strategy, and that of the control group who have been taught by the traditional method on the achievement test. The researcher adopted the post-test experimental design to measure students’ achievement. The population of the present study has been limited to the fifth literary class female students at the morning preparatory and secondary schools in the General Directorate of Educational AL-Rusafah 2. The sample of the study, which has been randomly selected, consists of (60) female students from the fifth literary class for AL-Fida Preparatory School distributed as follows (30) an experimental group, and (30) a control group .the Two groups have been equaled in (age, intelligence, pre-achievement scores in Geography course, and pre-knowledge in geography). The two groups of the present study have been exposed to tests. Data has been collected and then analyzed using proper statistical methods such as person correlation Coefficient, Alpha Cronbach formula, and t-test for two independent samples. The results revealed that the experimental group showed superior scores than the control group on the achievement test. In light of the research results, the researcher suggested conducting a study to identify the effect of teaching on the learning strategy reflected in other dependent variables such as systemic thinking.